Review on the effect of ceramic reinforcements with different weight percentage and process parameters on the mechanical properties of aluminium metal matrix composite - Lee, Jia En; Wong, Shih Jye; Lee, Woon Kiow; Talib, Norfazillah; Ong, Pauline; Abdullah, Haslina; Saleh, Aslinda; Mat Hassan, Normunira; Abd Rashid, Razlin (Penerbit UTHM, 2020)
In current modern engineering applications, aluminium metal matrix composites (AMMC) have been gaining more popularity in automobiles and aerospace industry due to their unique material properties offered such as low density and high strength to weight ratio. Fabrication of AMMCs can be achieved by embedding the reinforcement into metal matrix. Hybrid-AMMCs are getting more attention as they reinforced by a combination of two or more different type particulates in order to achieve the combined advantages of both of them. It was reported in many works that the hybrid composites of exhibited better properties than those reinforced only with single particulate (Awasthi et al., 2018; Mahmoud et al., 2010).